An Extension of the Systematic Layout Planning System Using Qdf: Its Application to Service Oriented Physical Distribution - Palominos-Belmar, P; Quezada-Llanca, L; Sanchez-Y Bernal, L (Taylor and Francis Ltd., 2019)
This work presents an original combination of the Systematic Layout Planning (SLP) methodology with Quality Function Deployment (QFD) for layout design of services. This methodology considers two stages. The first of these stages is Quality Function Deployment using the Modified Quality Matrix, and the second, the application of the various phases of the SLP method, using the data obtained during the first stage, in order to find a layout design which contains the client’s perception. The developed methodology was applied to redesign the layout plan for one academic department of the Universidad de Santiago de Chile. This application enabled the generation of alternative distributions, which were compared to the current layout, and the assessment was conducted by a team from the Department itself, using the Analytic Hierarchy Process (AHP). © 2019, © 2019 Taylor & Francis.